Investigation of the potential sources of water pollution affecting the companhia hidromineral Caldas da Imperatriz through physical, chemical, and biological analyses - Magnago, Rachel Faverzani; Pereira, Leopoldo Duarte; Freitas, Marcielly Melo; Ávila, Aline Ferreira Ali de; Silva, José Gabriel da (Ciência e Natura, 2018)
Water is an essential element for life. Accessing good quality and adequate water is directly linked to the people’s health. The aim of this study was to investigate the potential sources of water pollution affecting the Company Hidromineral Caldas da Imperatriz through physical, chemical, and biological analysis to reduce the risks of health hazards. Laboratory tests encompassed chemical parameters (pH, DO, BOD, nitrite, nitrate, and sulfate), physical parameters (color, turbidity and temperature), and biological parameters (total and thermotolerant coliforms). The results obtained were compared to the maximum values allowed by the CONAMA resolutions 357/2005 and 396/2008, and by Ordinance 2914/2011of the Ministry of Health. The analyzed parameters met the current legislation, except for the nitrite analysis performed on March 2, which presented alterations probably because of the rainfall during the previous days, and BOD for all samples, which was above the maximum value allowed by the CONAMA resolution 357/2005. Wastewaters from nearby hotels were the possible source of pollution affecting the waters of the Companhia Hidromineral Caldas da Imperatriz, since there were no other sources of anthropic pollution, such as plantations, livestock, and industries.